Is the local wheat market a ‘market for lemons’? Certifying the supply of individual wheat farmers in Ethiopia - Anissa, Banawe Plambou; Abate, Gashaw T.; Bernard, Tanguy; Bulte, Erwin (European Agricultural and Applied Economics Publications Foundation, 2021)
Bulking and mixing of smallholder supply dilutes incentives to supply high quality. We introduce wheat ‘grading and certification shops’ in Ethiopia and use an auction design to gauge willingness-to-pay (WTP) for certification. Bids correlate positively with wheat quality, and ex ante notification of the opportunity of certification improves wheat quality. These findings suggest that local wheat markets resemble a ‘market for lemons’, crippled by asymmetric information. However, aggregate WTP for grading and certification services does not re-coup the sum of fixed, flow and variable costs associated with running a single certification shop.